Mapping allele with resolved carrier status of Robertsonian and reciprocal translocation in human preimplantation embryos. (April 2019) - Xu, Jiawei; Zhang, Zhen; Niu, Wenbin; Yang, Qingling; Yao, Guidong; Shi, Senlin; Jin, Haixia; Song, Wenyan; Chen, Lei; Zhang, Xiangyang; Guo, Yihong; Su, Yingchun; et al.
Abstract : Introduction: Reciprocal translocations (RecT) and Robertsonian translocations (RobT) are among the most common chromosomal abnormalities that cause infertility and birth defects. Preimplantation genetic testing for aneuploidy using comprehensive chromosome screening for in vitro fertilization enables embryo selection with balanced chromosomal ploidy. However, it is normally unable to determine whether an embryo is a translocation carrier. We have reported a method named "Mapping Allele with Resolved Carrier Status" (MaReCs), which enables chromosomal ploidy screening and resolution of the translocation carrier status of the same embryo (J. Xu et al. 2017 ). Here we introduce MaReCs and update the clinical study results. Material & Methods: From September, 2017 to now, we have performed MaReCs on 69 patients, among them 55 were RecT carriers and 14 were RobT carriers. Result: Totally 176 embryos from patients were identified ploidy-balanced, of which embryos from 41 patients were successfully identified as normal or balanced translocation. Other embryos' translocation status could not be identified because of lacking reference embryos and these patients have accepted further identification in next cycles. And we have confirmed the accuracy of our carrier status determination in amniotic fluid karyotyping of seven cases as well as in the live birth we have thus far. Conclusions: MaReCs accurately enables the selection of translocation-free embryos from patients carrying chromosomal translocations. It can work as an effective technology to help reduce the propagation of RecT/RobT in the human population.